Within- and Cross-Firm Mobility and Earnings Growth. (March 2016) - Frederiksen, Anders; Halliday, Timothy; Koch, Alexander K.
A widely accepted premise is that promotions within firms and mobility across firms lead to significant earnings progression. Existing research generally has examined cross-firm mobility separately from hierarchical advancement. Yet, as the authors' descriptive evidence from Danish panel data shows, how the two types of mobility interact is important for understanding earnings growth. Cross-firm moves at the nonexecutive level provide sizable short-run earnings growth (similar to the effect of being promoted to an executive position). These gains, however, appear modest compared with the persistent impact on earnings growth of promotions (either within or across firms) and subsequent mobility at a higher hierarchy level.